The polarographic reduction and electrode kinetics of antiretroviral drug zidovudine - MAHIPAT SINGH; YOGESH KUMAR; ASHISH GARG; OMPRAKASH MEENA; RAJAYASHREE PANDEY (International Journal of Pharma and Bio Sciences, 2011)
The polarographic reduction of Zidovudine has been done in various conditions, at different temperatures, at different pH and at different concentrations by D. C. Polarography. The system is irreversible and exhibit diffusion controlled reduction. Single well defined irreversible wave obtained. So the kinetic parameters (K0 fh, αn) has been evaluated using Meites-Israel and Gaur-Bhargava’s method.